Penerapan Project based learning (PjBL) Menulis Teks Berita Siswa Kelas VII A SMP Negeri 16 Kota Jambi - Sari, Laura Meilita; Harahap, Eddy Pahar; Yusra, Hilman (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
This research aims to describe the implementation of the Project Based Learning model in learning to write news texts in class VII of SMP Negeri 16 Jambi City for the academic year 2023/2024, by looking at how to design, implement and assess learning outcomes in learning to write news. This research was conducted at SMP Negeri 16 Jambi City in January 2024. This research used qualitative phenomenological research. The subject of this research was a class VII Indonesian language teacher. Data analysis was carried out by testing data validity using source triangulation techniques. Data collection techniques are carried out by observation, interviews and documentation of research subjects and objects. The data analysis techniques in this research are, collecting data, data reduction, presenting data, verification and drawing conclusions. The results of the research show that the teacher implementing the Project Based Learning (PjBL) learning model has been implemented well in accordance with the PjBL steps, even though all the steps learning has been carried out well, but there are still several shortcomings in its implementation, namely the monitoring stage due to time limitations which can only be done during learning time, whereas when learning time runs out, educators cannot monitor students. However, students can still complete the project on time according to the schedule and produce good work